INFLUENCE OF BLOOD PLASMA MINERALS DURING ESTRUS ON CONCEPTION IN SAHIWAL CATTLE - AYAM, V B S; AWASTH, M K; TIWARI, R P; BHONSLE, D; GENDLY, M K (The Indian Journal of Animal Reproduction, 2015)
The present study was conducted to examine the influence of plasma levels of some macro-minerals and essentialtrace elements on conception in Sahiwal cattle. Blood plasma samples were collected from estrus cows (n=40) toestimate levels of macro-minerals viz. calcium, inorganic phosphorus and magnesium; and some essential traceelements viz. copper, cobalt, iron and zinc. Animals were inseminated 12 h after onset of estrus with good qualityfrozen semen. Significant differences (p
Keywords: Conception; Estrus; Plasma Minerals; Pregnancy